Are films inherently masculine? – the camera and representation of women as an act of terrorism. - Teo, Katherine Cheng Hoon. (2011)
The notion of phallogocentric implies that the binary of man/woman will always result in one term being preferred over the other. As Donna Haraway asserts in her essay titled A Manifesto for Cyborgs, “Gender, race or class consciousness is an achievement forced on us by the terrible historical experience of the contradictory social realities of patriarchy, colonialism, and capitalism”, and this consciousness is perpetuated through the notion of phallogocentrism (Haraway 591). Throughout history, women have always been seen as a negative relation to men – women are the oppressed and marginalized gender. So, when and how does patriarchal oppression take place? It takes place when men attempt to suppress women by subjugating them to a separate sphere and by defining them. Language serves as one of the ways in which this can be done and in this essay, I aim to analyze the ways in which cinema becomes another medium to undermine the feminine gender in which the camera becomes the tool for oppression. I aim to examine the dynamics of gender relationship in films that centers on sex and violence to determine if such films are inherently feminist and misogynist and how women are always positioned at a submissive position within the frames of the camera. The key question of this essay would be, “is the eye of the camera sexist and is films sexist? Can any plot be gender neutral?”